High‐Refractive‐Index Chip with Periodically Fine‐Tuning Gratings for Tunable Virtual‐Wavevector Spatial Frequency Shift Universal Super‐Resolution Imaging. Issue 9 (27th January 2022) - Tang, Mingwei; Han, Yubing; Ye, Dehao; Zhang, Qianwei; Pang, Chenlei; Liu, Xiaowei; Shen, Weidong; Ma, Yaoguang; Kaminski, Clemens F.; Liu, Xu; Yang, Qing
Abstract: Continued research in fields such as materials science and biomedicine requires the development of a super‐resolution imaging technique with a large field of view (FOV) and deep subwavelength resolution that is compatible with both fluorescent and nonfluorescent samples. Existing on‐chip super‐resolution methods exclusively focus on either fluorescent or nonfluorescent imaging, and, as such, there is an urgent requirement for a more general technique that is capable of both modes of imaging. In this study, to realize labeled and label‐free super‐resolution imaging on a single scalable photonic chip, a universal super‐resolution imaging method based on the tunable virtual‐wavevector spatial frequency shift (TVSFS) principle is introduced. Using this principle, imaging resolution can be improved more than threefold over the diffraction limit of a linear optical system. Here, diffractive units are fabricated on the chip's surface to provide wavevector‐variable evanescent wave illumination, enabling tunable spatial frequency shifts in the Fourier space. A large FOV and resolutions of λ /4.7 and λ /7.1 were achieved for label‐free and fluorescently labeled samples using a gallium phosphide (GaP) chip. With its large FOV, compatibility with different imaging modes, and monolithic integration, the proposed TVSFS chip may advance fields such as cell engineering, precision industry inspection, and chemical research. Abstract : A universal super‐resolution microscopy is developed based on tunable virtual‐wavevector spatial frequency shift that performs imaging on a single photonic chip, at a resolution three times better than the Abbe diffraction limit. Large field of view (FOV) imaging and resolutions of λ /4.7 for label‐free samples and λ /7.1 for fluorescently labeled samples with this chip are achieved. The micromodule can realize fast, large‐FOV, and deep subwavelength resolution imaging on an ordinary microscope when installed.